Cellulose Acetate-Based Wound Dressings Loaded with Bioactive Agents: Potential Scaffolds for Wound Dressing and Skin Regeneration - Ndlovu, Sindi P.; Alven, Sibusiso; Hlalisa, Kula; Aderibigbe, Blessing A. (Current Drug Delivery, 2024)
Wound healing and skin regeneration are major challenges in chronic wounds. Among the types of wound dressing products currently available in the market, each wound dressing material is designed for a specific wound type. Some of these products suffer from various shortcomings, such as poor antibacterial efficacy and mechanical performance, inability to provide a moist environment, poor permeability to oxygen and capability to induce cell migration and proliferation during the wound healing process. Hydrogels and nanofibers are widely reported wound dressings that have demonstrated promising capability to overcome these shortcomings. Cellulose acetate is a semisynthetic polymer that has attracted great attention in the fabrication of hydrogels and nanofibers. Loading bioactive agents such as antibiotics, essential oils, metallic nanoparticles, plant extracts, and honey into cellulose acetate-based nanofibers and hydrogels enhanced their biological effects, including antibacterial, antioxidant, and wound healing. This review reports cellulose acetate-based hydrogels and nanofibers loaded with bioactive agents for wound dressing and skin regeneration.
Keywords: skin regeneration